2013
DOI: 10.1073/pnas.1313677110
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, evolution, and diversity of retrotransposons at the flamenco locus reflect the regulatory properties of piRNA clusters

Abstract: Most of our understanding of Drosophila heterochromatin structure and evolution has come from the annotation of heterochromatin from the isogenic y; cn bw sp strain. However, almost nothing is known about the heterochromatin's structural dynamics and evolution. Here, we focus on a 180-kb heterochromatic locus producing Piwi-interacting RNAs (piRNA cluster), the flamenco (flam) locus, known to be responsible for the control of at least three transposable elements (TEs). We report its detailed structure in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(184 citation statements)
references
References 30 publications
14
159
0
Order By: Relevance
“…This region is a complex nest of fragmented TE sequences and is associated with the flam locus and production of piRNAs. Zanni et al (2013) reported that the Release 5 unmapped scaffold CP000194 (Release 5 U: 964336-1041768) containing piRNA cluster 17, includes a 30-kb segmental duplication of a portion of the flam locus. This scaffold is incorporated in Release 6 in the newly mapped scaffold between the two gaps in the X: 20B region.…”
Section: Discussionmentioning
confidence: 99%
“…This region is a complex nest of fragmented TE sequences and is associated with the flam locus and production of piRNAs. Zanni et al (2013) reported that the Release 5 unmapped scaffold CP000194 (Release 5 U: 964336-1041768) containing piRNA cluster 17, includes a 30-kb segmental duplication of a portion of the flam locus. This scaffold is incorporated in Release 6 in the newly mapped scaffold between the two gaps in the X: 20B region.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that piRNA-clusters exhibit structural polymorphism in different D. melanogaster strains. 52 In order to directly demonstrate the role of Hsp70 in the response of piRNA system to HS it is necessary to introduce one or several hsp70 genes into the hsp70-strain or alternatively introduce interference constructs inhibiting hsp70 genes into w 1118 strain (work in progress).…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the two cluster types extend far beyond the strand of transcription (Figure 1A). The transcription of uni-strand clusters seems to be similar to canonical mRNA transcription as these clusters have unique promoters and produce 5’ capped and polyadenylated RNA that are sometimes spliced [2931]. Dual-strand clusters produce non-polyadenylated RNA and the majority of dual-strand clusters does not have clear signatures of Pol II promoters, such as peaks of Pol II and H3K4me2 [3133].…”
Section: Nuclear Steps Of Pirna Biogenesismentioning
confidence: 99%